The Effect of Knowledge, Work Experience, and Work Spirit on Performance of Employees PT. Adira Dinamika Multifinance Pasuruan - Parmei Luluk Maliyah; Pompong B. Setiadi; Sri Rahayu (Dinasti Publisher, 2022)
As the relationship management perspective has been criticized and contradicting for focusing too much on individual entities, two parallel research tracks encourage business practices to view relational exchanges from a systems perspective. These two literary streams exist across the performance domain, sales force customization, sales force management, and sales to domain. The sales process can be seen as an episodic and non-linear exchange involving a large number of stakeholders. Our systematic review of the sales literature reveals a rich science that parallels the above characteristics. At the same time, this research fails to integrate management school perspectives or to identify links that illustrate the foundations of neoliberalism and improved the welfare states. We aim to develop a middle-class theory of the well-being of the sales ecosystem by combining the sales performance and performance of the sales ecosystem that can be targeted to this emerging of increasing the sales insurance product